(untitled) (Research, Society and Development, 2020)
The bananas from cv. BRS Vitória, were developed to be resistant to pests and offer sensory and nutritional characteristics to consumers, however, their use in processing can be restricted only when they are ripe. The work evaluated the physical, physical-chemical characteristics and bioactive compounds of bananas cv. BRS Vitória, in a high stage of maturation. The bananas were class 15 with an average of 15.17 cm in length and yellow in color with brown spots, presented constitution within the parameters established by MAPA for banana pulp with averages of 0.31 % for ATT, 4.74 pH, 24.00 ° Brix, SST/ATT ratio of 76.80, AT and RA of 19.21 %, humidity of 77.22%, ash of 5,30 %, being characterized as a good source of minerals. Regarding the bioactive quantity, bananas stood out for presenting 147.75 mgEAG.100g-1, being considered a high polyphenol index. Thus, we conclude that bananas cv. BRS Vitória, even at a high stage of maturity, have acceptable quality characteristics. However, the use for fresh consumption and processing can occur even at a high stage of maturity.